A research note on multinationality and firm performance: Nonparametric frontier analysis. Issue 10 (2nd October 2017) - Grant, Kevin; Mateousek, Roman; Meyer, Martin; Tzeremes, Nickoloas G.
Abstract : Purpose: The purpose of this paper is to provide a fresh insight into the examination of the comparison between multinationality and firm performance, measured through technical efficiency levels by overcoming methodological constraints and misunderstandings presented in earlier research. Design/methodology/approach: The authors estimate firms' efficiency levels in a production function-type framework through technical efficiency levels using nonparametric data envelopment analysis. The authors include firms from both developed and developing economies, from different national origins and with different sectoral characteristics, with a particular focus on knowledge-intensive business services (KIBS) and capital-intensive business services (CIBS). Findings: The study confirms for the case of KIBS the existence of the three-stage sigmoid (S-shaped) hypothesis between multinationality and firm performance measured through technical efficiency levels. Finally, the empirical findings reveal that CIBS exhibit only the first two stages, thus forming a "U"-shape relationship. Originality/value: The authors propose the application of different firms' performance measurements, providing us with the ability to unpack a firms' managerial decision processes with regards to determining the optimised investment(s) in technology and research and development and with a particular focus on KIBS and CIBS.